Libraries Driving Access to Knowledge - Bothma, Theo J. D. (2012)
This book is a must for librarians with international interest in access to knowledge. It includes a collection of 15 chapters written by authors from all over the world and covers different approaches to the vital role of libraries driving access to knowledge. There are chapters that offer solutions and ideas to enable libraries to become the knowledge engine in society. Other chapters discuss the conceptual part of the subject and related services. The book was compiled as part of the presidential theme of Ellen Tise, IFLA President 2009-2011, with the aim of offering the reader a good portrait of the opportunities and challenges that libraries have in driving access to knowledge...